Acute effects of direct inhibitory pressure over the biceps brachii myotendinous junction on skeletal muscle activation and force output. (December 2017) - Cè, Emiliano; Longo, Stefano; McCoy, Emily; Bisconti, Angela Valentina; Tironi, Davide; Limonta, Eloisa; Rampichini, Susanna; Rabuffetti, Marco; Esposito, Fabio
Abstract: Force (F) reduction is reported with myotendinous junction (MTJ) manipulation. Autogenic inhibition reflex (AIR) activation is supposed to be the main mechanism. Still, its role remains unclear. The study aimed at assessing the effects of MTJ direct inhibitory pressure (DIP) on neuromuscular activation and F in the elbow flexor (agonist) and extensor (antagonist) muscles. After maximum voluntary contraction (MVC) assessment, thirty-five participants randomly performed submaximal contractions at 20, 40, 60, and 80% MVC. Electromyographic (EMG), mechanomyographic (MMG), and F signals were recorded. Protocol was repeated under (i) DIP (10-s pressure on the biceps brachii MTJ) with the elbow at 120° (DIP120 ), (ii) DIP with the elbow at 180° (DIP180 ), and (iii) without DIP (Ctrl). Electromechanical delay (EMD) components, EMG and MMG root mean square (RMS), and rate of force development (RFD) were calculated. Independently from the angle, DIP induced decrements in MVC, RFD, and RMS of EMG and MMG signals and lengthened the EMD components in agonist muscles ( P  < 0.05). The DIP-induced decrease in F output of the agonist muscles seems to be possibly due to a concomitant impairment of the neuromuscular activation and a transient decrease in stiffness. After DIP, the antagonist muscle displayed no changes; therefore, the intervention of AIR remains questionable.